Alteration of Brain Structure With Long-Term Abstinence of Methamphetamine by Voxel-Based Morphometry - Zhang, Zhixue; He, Lei; Huang, Shucai; Fan, Lidan; Li, Yining; Li, Ping; Zhang, Jun; Liu, Jun; Yang, Ru (Frontiers in Psychiatry, 2018)
Background: A large portion of previous studies that have demonstrated brain grey matter reduction in individuals who use methamphetamine (MA) have focused on short-term abstinence, but few studies have focused on the effects of long-term abstinence of methamphetamine on brain structures. Materials and Methods: Our study includes 40 healthy controls and 44 abstinent methamphetamine-dependent (AMD) subjects who have abstained for at least 14 months. For every AMD subject, the age when they first used MA, the total time of MA use, the frequency of MA use in the last month before abstinence, the duration of abstinence and the craving score were recorded. Here we used magnetic resonance imaging (MRI) to measure the grey matter volume (GMV) of each subject with voxel-based morphometry method. Two-sample t-test (AlphaSim corrected) was performed to obtain brain regions with different grey matter volume (GMV) between groups. In addition, partial correlation coefficients adjusted for age, years of education, smoking and drinking were calculated in the AMD group to assess associations between the mean GMV values in significant clusters and variables of MA use and abstinence. Results: Compared with the healthy control group, AMD group showed increased grey matter volumes in the bilateral cerebellum and decreased volumes in the right calcarine and right cuneus. Moreover, GMV of left cerebellum are positively correlated with the duration of abstinence in the AMD group (p=0.040, r=0.626). Conclusions: The present study showed that the grey matter volume in some brain regions is abnormal in the AMD subjects with long-term abstinence. Changes in grey matter volume of visual and cognitive function regions suggested that these areas play important roles in the progress of MA addiction and abstinence. In addition, positive correlation between GMV of the left cerebellum crus and duration of abstinence suggested that prolonged abstinence is beneficial to cognitive function recovery.